Reimagining communication: action - Filimowicz, Michael 1971-; Tzankova, Veronika (Routledge, Taylor & Francis Group, 2021)
"Reimagining Communication: Action investigates the practical implications of communication as a cultural industry, media ecology, and a complex social activity integral to all domains of life. The Reimagining Communication series develops a new information architecture for the field of communications studies, grounded in its interdisciplinary origins and looking ahead to emerging trends as researchers take into account new media technologies and their impacts on society and culture. A diverse body of contributions in this unique interdisciplinary resource explore communication as a form of action within a mix of social, cultural, political, and economic contexts. They emphasize the continuously expanding horizons of the field by engaging with the latest trends in practical inquiry within communication studies. Reflecting on the truly diverse implications of communicative processes and representations, Reimagining Communication: Action covers key practical developments of concern to the field. It integrates diverse theoretical and practice-based perspectives to emphasize the purpose and significance of communication to human experience at individual and social levels in a uniquely accessible and engaging way. This is an essential introductory text for advanced undergraduate and graduate students and scholars of communication, broadcast media, and interactive technologies, with an interdisciplinary focus and an emphasis on the integration of new technologies"